Robert Schumann’s biography as seen by psychiatrist - Kusz, Wojciech (Current Problems of Psychiatry, 2011)
Robert Schumann (1810-56), the legendary romantic composer, writer, journalist, founder of manager of the musical journal “Neue Zeitschrift für das Musik”. The first, who made known genius of Chopin (1830, Hafts oft to Genius). Following a meeting with Brahms (1853) he noted in his diary: “Meeting with Brahms, his a genius”. A sufferer since his treaties headaches and low mood, at the age of 21/22 he lost the use of the 3rd and 4th finger of his right hand. Periods of great activity, including his compositions were interspersed creative disability connected with increasing suffering eased by depressive mood. Since his 30’s he also experienced periodic hallucination and difficulties with mobility. After an attempted suicide in Feb 1854 he requested to be send to a mental hospital in Endenich near Bonn where he remained for the rest of his life. Given that these events took place almost 50 years before Krae-pelin (1896) and considering the lack of contemporary expression of symptoms it’s impossible to describe the certain diagnosis. The bipolar mood disturbance in form of ME seems to be the most visible consideration.